Empirical evidence of phishing menace among undergraduate smartphone users in selected universities in Nigeria - Maureen Ifeanyi Akazue; Arnold Adimabua Ojugo; Rume Elizabeth Yoro; Bridget Ogheneovo Malasowe; Obinna Nwankwo (Institute of Advanced Engineering and Science, 2022)
In our exploratory quasi-experimental study, 480-student were recruited and exposed to social engineering directives during a university orientation week. The directives phishing attacks were performed for 10 months in 2021. The contents attempted to elicit personal user-data from participants, enticing them to click compromised links. The study aimed to determine cybercrime risks among undergraduates in selected universities in Nigeria, observe responses to socially-engineered attacks, and explore their attitudes to cybercrime risks before/after such attacks. The study generalized that all participants have great deal awareness of cybercrime, and also primed all throughout study to remain vigilant to scams. The study explores various types of scam and its influence on students’ gender and age on perceived safety on susceptibility to phishing scams. Results show that contrary to public beliefs, none of these factors were associated with scam susceptibility and vulnerability rates of the participants.